Deurle 11/7/73. - André, Carl; Baldessari, John; Barry, Robert; Benjamin, Walter; Broodthaers, Marcel; Burgin, Victor; Burn, Ian; Cadere, Andre; Graham, Dan; Huebler, Douglas; Kosuth, Joseph; LeWitt, Sol; et al. (Deurle : MDD (museum Dhondt-Dhaenens) Deurle, 1973)
Andre, Carl ; Baldessari, John ; Barry, Robert ; Broodthaers, Marcel ; Burgin, Victor ; Burn, Ian ; Cadere, Andre ; Graham, Dan ; Huebler, Douglas ; Kosuth, Joseph ; LeWitt, Sol ; Ramsden, Mel ; Romeu, Joost A. ; Ryman, Robert ; Weiner, Lawrence ; Wilson, Ian
Nederlands
boek